POSTOPERATIVE COMPLICATIONS RATE IN EARLY AND LATE PRESENTING CASES OF GASTROINTESTINAL TRACT PERFORATION IN BIHAR: A COHORT STUDY. - Tanweer Alam (Student's Journal of Health Research Africa, 2024)
Background Gastrointestinal (GI) tract perforation is a life-threatening surgical emergency requiring immediate intervention. This study aims to evaluate the postoperative complication rates in early versus late presenting cases of gastrointestinal tract perforations in Northern India. Methods A prospective cohort study included 182 individuals with confirmed GI tract perforations, who presented to the emergency department and outpatient clinic. The patients were allotted into 2 groups: Group A (presentation within 48 hours) and Group B (presentation between 48 and 144 hours). Both groups underwent exploratory laparotomy followed by standard postoperative care. Data on postoperative complications, hospital stay, and mortality were collected and analyzed using SPSS version 23.0. Results The study included 182 patients, with 48 in Group A and 134 in Group B. The mean age was 42.5 ± 10.6 years, with a male predominance (70% male, 30% female). Group B experienced significantly higher rates of postoperative complications compared to Group A. Local complications, such as surgical site infection, were observed in 25.4% of Group B patients versus 10.4% in Group A (p=0.028). Systemic complications, including septicemia and respiratory complications, were more common in Group B (55.2%) compared to Group A (27.1%) (p=0.001). The mortality rate was significantly higher in Group B (17.9%) compared to Group A (6.2%) (p=0.047). The mean hospital stay was longer for Group B, averaging 12.6 ± 4.3 days, compared to 8.9 ± 3.1 days for Group A (p<0.001). Conclusion Delayed presentation of GI tract perforations is correlated with notably higher postoperative complications, longer hospital stays, and increased mortality. Early intervention is crucial to improving patient outcomes. Recommendations There is an urgent need to enhance healthcare accessibility and education in rural areas to encourage early presentation. Strengthening healthcare infrastructure and implementing community outreach programs can help reduce delays in seeking medical care for GI emergencies.